2008
DOI: 10.1007/s10334-008-0156-9
|View full text |Cite
|
Sign up to set email alerts
|

High resolution magic angle spinning NMR spectroscopy for metabolic assessment of cancer presence and Gleason score in human prostate needle biopsies

Abstract: This preliminary study indicates that HRMAS NMR of routinely obtained PNBs can provide detailed metabolic information of intact prostate tissue with clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 32 publications
7
72
1
Order By: Relevance
“…Although not the main objective of this study, we present results supporting the inverse correlation between the citrate signal and the Gleason score (6,31,32). In cancer samples with equal amounts of benign epithelium and stroma, we observed lower citrate levels in high-risk samples (Gleason score >8) than in low-risk samples (Gleason score ¼ 6; Fig.…”
Section: Tissue Heterogeneity and Tumor Aggressivity Assessmentsupporting
confidence: 76%
“…Although not the main objective of this study, we present results supporting the inverse correlation between the citrate signal and the Gleason score (6,31,32). In cancer samples with equal amounts of benign epithelium and stroma, we observed lower citrate levels in high-risk samples (Gleason score >8) than in low-risk samples (Gleason score ¼ 6; Fig.…”
Section: Tissue Heterogeneity and Tumor Aggressivity Assessmentsupporting
confidence: 76%
“…In particular, it proved to be very powerful for corroborating and complementing noninvasive in vivo magnetic resonance spectroscopy studies by aiding assignment and quantification of the in vivo data, generally characterised by poor resolution and signal-tonoise at clinical magnetic field strengths [10][11][12][13][14]. Moreover, much research work has focused on the metabolic differentiation between tumour and healthy tissues, aiming to find possible biomarkers for the presence and/or grade of different cancers such as breast [15,16], brain [17,18], prostate [19][20][21], cervical [22][23][24], colorectal [25,26], hepatic [27], renal [28,29] and gastric cancer [30].…”
Section: Introductionmentioning
confidence: 98%
“…Finally, it is interesting to mention the work of Asten et al in which it is demonstrated that the prostate biopsy tissue is not altered after the analysis by HR-MAS, so it can be used for histological diagnosis [8].…”
Section: Prostatementioning
confidence: 99%